Ultrasonic-assisted fast upgrading of heavy crude oil using novel nanofluids - Luay Ahmed Khamees; Ayad A. Alhaleem; Ghassan H. Abdul-Majeed (South African Journal of Chemical Engineering)
Upgrading heavy crude oil is essential for enhancing its flow properties, refining efficiency, and economic value, especially given its high viscosity and elevated levels of sulfur and heavy metals. This study investigates the effectiveness of four kerosene-based nanofluids—containing alumina, zirconia, silica, and iron oxide nanoparticles- in improving the quality of heavy crude oil from the East Baghdad oil field. The nanofluids were first evaluated for stability using transmission electron microscopy (TEM) and were then applied to crude oil samples through ultrasonication. Among the tested fluids, alumina-based nanofluids exhibited the highest performance, achieving a 90.4 % reduction in viscosity and significant improvements in API gravity and impurity removal. Vanadium content was reduced by 92 %, nickel by 85 %, and sulfur by 83 %. The other nanofluids also yielded promising results, with zirconia, silica, and iron oxide achieving sulfur reductions of 79 %, 76 %, and 73 % respectively. Notably, this approach offers an environmentally conscious alternative to conventional methods by significantly lowering sulfur levels, thereby contributing to reduced emissions of harmful pollutants. In addition to its technical advantages, the proposed method is cost-effective and scalable, utilizing affordable kerosene instead of expensive organic solvents. These findings demonstrate the potential of integrating nanotechnology with ultrasonication as a sustainable and efficient strategy for heavy crude oil upgrading in modern energy systems.